The development of the AWIN welfare assessment protocol for donkeys - Dalla Costa, Emanuela (2021)
The donkey population has increased in the last 10 years, with an estimated 50 million donkeys currently worldwide. Donkey welfare, meanwhile, is an increasing global concern that receives close public scrutiny. However, multiple challenges are surrounding how donkey welfare is assessed and recorded. The Animal Welfare Indicators (AWIN) project is the first project, funded by the European Commission, intended to improve donkey welfare by developing a scientifically sound and practical on-farm welfare assessment protocol. The present study describes the procedure for the development of the AWIN welfare assessment protocol for donkeys: 1) selection of promising welfare indicators; 2) research to cover gaps in knowledge; 3) stakeholder consultation; 4) testing the prototype protocol on-farm. The proposed two-level strategy improved on-farm feasibility, while the AWIN donkey app enables the standardized collection of data with prompt results. Although limitations are linked with a relatively small reference population, the AWIN welfare assessment protocol represents the first scientific and standardized approach to evaluate donkey welfare on-farm.